Chromene flavanones from Dalea boliviana as xanthine oxidase inhibitors: in vitro biological evaluation and molecular docking studies - Bedoya Aguirre, Einy Nallybe; Santi, María Daniela; Negro, Melisa Fabiana; Echeverría, Javier; Paulino Zunini, Margot; Peralta, Mariana Andrea; Ortega, María Gabriela (Frontiers in Pharmacology, 2025)
BackgroundPrenylated flavanones represent a structurally diverse class of natural compounds with significant biological potential. Among them, chromene flavanones (CFs) constitute a rare and specialized subgroup with promising therapeutic applications. These molecules have gained attention due to their potential to inhibit xanthine oxidase (XO), a key enzyme involved in oxidative stress-related disorders such as gout and hyperuricemia. Their distinctive structural features, combined with notable bioactivity, make them compelling candidates for further pharmacological exploration. Given their potential relevance, this study focuses on the in vitro and in silico evaluation of three CFs isolated from Dalea boliviana Britton [Fabacea], assessing their capacity to inhibit XO and elucidating key structure–activity relationships (SARs) that contribute to their biological effectiveness.PurposeThis study aims to investigate the in vitro and in silico interactions of the chromene flavanones, namely, (2S) 5,2′-dihydroxy-6″,6″-dimethylchromeno-(7,8:2″,3″)-flavanone (1), (2S) 5,2′-dihydroxy-6″,6″-dimethylchromeno-(7,8:2″,3″)-3′-prenylflavanone (2), and obovatin (3), obtained from D. boliviana, with XO, in order to explore their potential as XO inhibitors and their potential therapeutic applications for hyperuricemic diseases.Material and MethodsXO inhibition by the three chromene flavanones was measured spectroscopically. The relationships between their structures and inhibitory activities were evaluated. Moreover, molecular docking studies were performed to propose the binding modes of the most active natural compounds.Results and discussionCompounds 1 and 2 exhibited potent inhibition, with IC50 values in the nanomolar range (0.5 ± 0.01 nM and 1.7 ± 0.46 nM, respectively), demonstrating significantly higher activity than allopurinol (AL), the reference inhibitor (IC50 = 247 ± 4 nM). In contrast, compound 3 displayed only weak inhibition. SAR analysis revealed that the presence of a chromene moiety in the A-ring, combined with hydroxyl and prenyl groups in the B-ring, played a crucial role in enhancing inhibitory activity. Molecular docking studies confirmed the strong binding affinities of compounds 1 and 2 within the active site of XO (PDB ID: 3NVY), with binding energies of −6.1687 kcal/mol and −6.7820 kcal/mol, respectively. Key stabilizing interactions involved π–π interactions with Phe914 and hydrogen bonding with residues such as Leu873 and Leu1014. These findings highlight the structural features essential for potent XO inhibition and suggest that chromene flavanones represent a valuable scaffold for the development of novel inhibitors. Further molecular dynamics simulations could provide deeper insights into their stability and interaction dynamics, aiding in the rational design of more effective XO inhibitors.ConclusionOur findings lead us to propose these chromene flavanones as lead compounds for the design and development of novel XO inhibitors for treating diseases in which exacerbated activity of this enzyme is involved.